2012
DOI: 10.3109/00365599.2012.727859
|View full text |Cite
|
Sign up to set email alerts
|

Combination of real-time elastography and urine prostate cancer gene 3 (PCA3) detects more than 97% of significant prostate cancers

Abstract: The combination of PCA3 score and RTE detected 97% of significant prostate cancers. The combinative use of RTE and PCA3 will be further investigated in an unselected series of men with suspected prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 18 publications
2
10
0
Order By: Relevance
“…Maybe this multiparametric way—adding tissue informations about contrast media dynamics to grey-scale ultrasound and RTE—could have detected some of our false negative findings. Brock et al have shown the usefulness of this approach, whereas Nygård et al demonstrated the benefit of adding new biomarkers, like PCA-3, to RTE findings for the detection of significant disease [24, 25]. …”
Section: Discussionmentioning
confidence: 99%
“…Maybe this multiparametric way—adding tissue informations about contrast media dynamics to grey-scale ultrasound and RTE—could have detected some of our false negative findings. Brock et al have shown the usefulness of this approach, whereas Nygård et al demonstrated the benefit of adding new biomarkers, like PCA-3, to RTE findings for the detection of significant disease [24, 25]. …”
Section: Discussionmentioning
confidence: 99%
“…Nygård et al demonstrated the benefit of adding new biomarkers, like PCA-3, to RTE findings for the detection of significant disease [37]. …”
Section: Rte Before Radical Prostatectomy (Rpe)mentioning
confidence: 99%
“…The prostate was divided into six peripheral zone (PZ) regions excluding the transition zone (TZ) from the investigation . Each region was examined for cancer suspicious lesions with both methods starting with B‐mode.…”
Section: Methodsmentioning
confidence: 99%
“…The prostate was divided into six peripheral zone (PZ) regions excluding the transition zone (TZ) from the investigation [8].…”
Section: Us Rte Targeted Biopsies Standard Biopsies and Report Formsmentioning
confidence: 99%